ChatGPT and its ethical implications for STEM research and higher education: a media discourse analysis - Benjamin H. Nam; Qiong Bai (SpringerOpen, 2023)
Abstract Background With the increasing demand brought on by the beginning of the fourth industrial revolution in the period of post-digital education and bio-digital technology, artificial intelligence (AI) has played a pivotal role in supporting human intelligence and contributing to intellectuals within science, technology, science, and mathematics (STEM) and in the broader field of higher education. Thus, this study examines how writers for mainstream STEM journals and higher education magazines perceive the impact of ChatGPT, a powerful AI chatbot, on STEM research and higher education. ChatGPT can generate realistic texts based on user prompts. However, this platform also poses ethical challenges for academic integrity, authorship, and publication. Results Using a comparative media discourse analysis approach, this study analyzes 72 articles from four media outlets: (a) Springer Nature; (b) The Chronicle of Higher Education; (c) Inside Higher Ed; and (d) Times Higher Education. The results show that the writers expressed various concerns and opinions about the potential conflicts and crises caused by ChatGPT in three areas: (a) academic research and publication; (b) teaching and learning; and (c) human resources management. Conclusions This study concludes with some policy implications and suggestions for future research on ChatGPT and AI ethics in academia by reilluminating the most overarching policy concerns related to ethical writing in STEM research and higher education and limitations to the blindness to authorship and academic integrity among diverse stakeholders.